Miniaturization Of Balanced Low Noise Amplifier For Wimax Application - Nekeram, Nitesh Ram Sharma (2010)

(untitled)
Demands for broadband wireless communications has been growing fast recently with the advent of new technologies such as WiMAX. With this growing demand, RF transceiver manufacturers are constantly challenged with the requirements to provide compact and wideband RF components. One such important component especially for WiMAX base-station is the LNA. Current balanced LNAs used in WiMAX base-station is huge in size due to the low frequency of operation which is from 2.3GHz to 2.7GHz. The main objective of this research is to reduce the size of the balanced LNA in an attempt to reduce the cost of the WiMAX base-station.